Two Millennia of Complexity and Variability in a Perialpine Socioecological System (Savoie, France): The Contribution of Palynology and sedaDNA Analysis - Messager, Erwan; Giguet-Covex, Charline; Doyen, Elise; Etienne, David; Gielly, Ludovic; Sabatier, Pierre; Banjan, Mathilde; Develle, Anne-Lise; Didier, Julien; Poulenard, Jérôme; Julien, Andréa; Arnaud, Fabien (Frontiers in Ecology and Evolution, 2022)
Over the last two millennia, European Alpine ecosystems have experienced major changes in response to the important, yet fluctuating, impact of human activities. This study aims to reconstruct the environmental history of the last 1800 years on the western edge of the Alps by analyzing sediments from Lake Aiguebelette, a large lake located in the perialpine area. We have combined analyses of pollen and other palynomorphs, such as coprophilous fungal spores, together with sedimentary DNA (from plants and mammals) in order to reconstruct both vegetation and land-use histories. A sedimentological and geochemical analysis was also conducted in order to gain an understanding of changes in erosion dynamics in response to landscape modifications that were influenced by climate and human activities. This work highlights alternating phases of anthropization and agricultural abandonment allowing forest recovery. While pollen reflects the major phases of regional deforestation and afforestation related to the dynamic of farming activities, plant DNA provides precise information on the plants cultivated in fields, orchards and vegetable gardens over the past centuries. The combination of mammal DNA and coprophilous fungal spores completes this work by documenting the history of pastoral practices.